The Multifaceted Roles of Primary Cilia in the Development of the Cerebral Cortex - Hasenpusch-Theil, Kerstin; Theil, Thomas (Frontiers in Cell and Developmental Biology, 2021)
The primary cilium, a microtubule based organelle protruding from the cell surface and acting as an antenna in multiple signaling pathways, takes center stage in the formation of the cerebral cortex, the part of the brain that performs highly complex neural tasks and confers humans with their unique cognitive capabilities. These activities require dozens of different types of neurons that are interconnected in complex ways. Due to this complexity, corticogenesis has been regarded as one of the most complex developmental processes and cortical malformations underlie a number of neurodevelopmental disorders such as intellectual disability, autism spectrum disorders, and epilepsy. Cortical development involves several steps controlled by cell–cell signaling. In fact, recent findings have implicated cilia in diverse processes such as neurogenesis, neuronal migration, axon pathfinding, and circuit formation in the developing cortex. Here, we will review recent advances on the multiple roles of cilia during cortex formation and will discuss the implications for a better understanding of the disease mechanisms underlying neurodevelopmental disorders.